Juridical Analysis Of Settlement Of Land Disputes Through Decisions Of Customary Institutions - Asriadi, Asriadi; Sara, Rineke; Fakrulloh, Zudan Arief (Journal Research of Social Science, Economics, and Management, 2023)
The land is a natural resource that has a very important role because the land is needed by humans for various kinds of life interests such as living, farming, trying, and so on. The policy for the development of the land sector in Indonesia is essentially rooted in the provisions of the 1945 Constitution Article 33 paragraph (3) which reads "Earth, water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people". To guarantee legal certainty in the field of land, Article 19 paragraph (1) of the UUPA stipulates: "To guarantee legal certainty, the government will carry out land registration throughout the territory of the Republic of Indonesia according to the provisions stipulated by government regulations". Even though it has been regulated in such a way, the problem of land disputes continues and will forever occur due to conflicts of various interests. In customary law communities, disputes that occur are resolved by deliberation and consensus through customary institutions. This study aims to determine (1) the existence of Customary Institutions in resolving disputes in indigenous peoples, and (2) the authority of customary institutions in resolving disputes in customary law communities.